2020
DOI: 10.1063/5.0019296
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude-modulated resonant accelerometer employing parametric pump

Abstract: This paper demonstrates a resonant accelerometer employing weakly coupled resonators for inertial force transduction. An ultra-low virtual mode coupling is established by employing the parametric pump in the coupled resonators to enhance the parametric sensitivity. This paper proposes that the amplitude of the driven resonator can be used for monitoring the input acceleration in a limited linear range around the veering point. In addition to the high-sensitivity improvement, the measurement complexity is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The resolution of the peak detector circuit was defined by a distinguishable change of the modulated DC voltage signal subjects to the mass perturbation on the QCM. The proposed hybrid mass sensing system has the potential to achieve a resolution of about 6 ng by adopting the techniques reported in [29,30], which are based on the non-linear behaviour of the coupled resonator and an interface circuitry with low noise floor.…”
Section: Resultsmentioning
confidence: 99%
“…The resolution of the peak detector circuit was defined by a distinguishable change of the modulated DC voltage signal subjects to the mass perturbation on the QCM. The proposed hybrid mass sensing system has the potential to achieve a resolution of about 6 ng by adopting the techniques reported in [29,30], which are based on the non-linear behaviour of the coupled resonator and an interface circuitry with low noise floor.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike direct excitation applied to the resonators, parametric excitation as an alternative method is suggested to actuate M/NEMS resonators, which modulates the entire restoring force (including linear and nonlinear terms) as a function of time. Some studies have considered this technique [24,34,[267][268][269][270][271][272][273] to achieve large distinctive responses since many excitation methods including electrostatic actuation in M/NEMS field allow natural parametric excitation. The most basic model for this class of resonators is related to the linear Mathieu equation including a time-varying stiffness component.…”
Section: Parametric Excitationmentioning
confidence: 99%
“…The practical implementation is still very problematic and needs further improvements in spite of the significant advantages for the mode-localized sensors, which resulted in conducting further studies to improve the performance of mode-localized devices and reduce their restrictions. [272,273,[411][412][413][414][415] For instance, Zhao et al [413] demonstrated an optimal operating region for improving the resolution of amplitude ratio measurements. Further, a minimum noise floor of ≈16 ppbHz −1/2 was obtained in terms of normalized stiffness perturbation by optimizing the coupling strength and initial stiffness mismatch.…”
Section: Amplitude Shift-based Crasmentioning
confidence: 99%
“…Previous solutions to a similar problem [35] showed that when f BSE ≈ f 1 + f 2 , numerical solutions of u 1 and u 2 exist simultaneously; therefore, both modes 1 and 2 can be excited by the BSE signal. The term 'blue-sideband' is used here, which is contrary to recent studies of parametric modulation using a red-sideband modulation signal, f red ≈ f 2 − f 1 [36]- [38], in which energy is transferred between the two modes.…”
Section: Blue-sideband Excitationmentioning
confidence: 99%